Detecção de Alouatta belzebul por DNA ambiental e DNA derivado de invertebrados no Centro de Endemismo Pernambuco - Olímpio, Leonardo Willian Gonçalves Ferreira (Universidade Federal de São Carlos, 2024)
The species Alouatta belzebul, known as the red-handed howler monkey, is classified as Vulnerable to extinction and occurs in the Amazon and the Pernambuco Endemism Center (PEC), a highly devastated segment of the Atlantic Forest located north of the São Francisco River mouth. Habitat fragmentation is one of the main threats to the conservation of this primate, affecting its distribution and behavior, such as vocalization and movement. One of the primary objectives of this research was to validate non-invasive methods for detecting the species in forest fragments of the PEC, located in the states of Alagoas, Paraíba, and Rio Grande do Norte, using water samples and the stomach content of flies and mosquitoes, through the employment of environmental DNA (eDNA) and invertebrate-derived DNA (iDNA) approaches, respectively. Additionally, a species distribution modeling (SDM) analysis was employed to predict potential occurrence areas of the species, using relevant environmental variables, such as precipitation, temperature, and land cover. The combined use of these methodologies proved to be an effective alternative for identifying the species and predicting its occurrence areas, contributing to the effective monitoring and conservation of the species. The results showed that iDNA enabled the detection of A. belzebul in the study area, revealing new areas of occurrence in Alagoas and Pernambuco. Modeling analyses indicated that areas with higher canopy height and tree cover are essential for the conservation of the species. The relationship between the species' presence and environmental variables highlights the importance of habitat integrity for the survival of A. belzebul. These findings can help identify areas most suitable for the creation of ecological corridors and critical or priority areas for the conservation of the species, supporting public policies aimed at the conservation of the species in the PEC. Thus, the results of this study not only add relevant information about the current and potential distribution of A. belzebul in the PEC but also prove useful for guiding management and monitoring actions for the species. Additionally, the combined use of alternative methods for species detection, such as eDNA and iDNA, with species distribution modeling analyses employed in this study constitutes a relevant model that can be applied to other threatened species in fragmented regions similar to the one studied. This work, therefore, advances not only the knowledge about the distribution and ecology of A. belzebul but also provides practical tools aimed at the monitoring and conservation of biodiversity.
Detection of Alouatta belzebul via environmental DNA and invertebrate-derived DNA in the Pernambuco Endemism Center
Keywords: Fragmentação de habitat; Mata Atlântica; Genética da conservação; Modelagem de distribuição de espécies; Novas ocorrências; Habitat fragmentation; Atlantic forest; Conservation genetics; Species distribution modeling; New records; CIENCIAS BIOLOGICAS::GENETICA::GENETICA ANIMAL; CIENCIAS BIOLOGICAS::ZOOLOGIA::ZOOLOGIA APLICADA::CONSERVACAO DAS ESPECIES ANIMAIS